2009
DOI: 10.1016/j.dsp.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Doppler spectrum estimation by Ramanujan-Fourier Transform (RFT)

Abstract: Abstract.The Doppler spectrum estimation of a weather radar signal in a classic way can be made by two methods, temporal one based in the autocorrelation of the successful signals, whereas the other one uses the estimation of the power spectral density PSD by using Fourier transforms. We introduces a new tool of signal processing based on Ramanujan sums cq(n), adapted to the analysis of arithmetical sequences with several resonances p/q. These sums are almost periodic according to time n of resonances and aper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, the peculiarity of AD-plane is that, in this domain the signal terms appear localized around the origin and the cross-terms are located away from the origin [14]. In this work, a modified AF representation is computed by using the RS (on the time-varying autocorrelation values) as (8) Such a computation results in an overall reduction in the number of AD coefficients. These AD-mapped coefficients can then be transformed into a sparser time-frequency representation, using the RFT computed from their characteristic RS.…”
Section: B Rationalementioning
confidence: 98%
See 1 more Smart Citation
“…However, the peculiarity of AD-plane is that, in this domain the signal terms appear localized around the origin and the cross-terms are located away from the origin [14]. In this work, a modified AF representation is computed by using the RS (on the time-varying autocorrelation values) as (8) Such a computation results in an overall reduction in the number of AD coefficients. These AD-mapped coefficients can then be transformed into a sparser time-frequency representation, using the RFT computed from their characteristic RS.…”
Section: B Rationalementioning
confidence: 98%
“…Their research showed that in the presence of Gaussian noise, RFT captures the signal periodicities better than the conventional DFT. Lagha et al [8] expanded on the theory of usability of this transform for estimation of Doppler spectral parameters for weather signals. The usefulness of this class of transform is also reported for analysis of biomedical signals, such as T-wave alternans, by Mainardi et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…These base functions satisfy many suitable properties for signal decomposition such as multiplicative and orthogonality properties. Alternatively, the Ramanujan sums can be evaluated using the Euler totient function φ(q) and Moebius function µ(n) as follows (Lagha and Bensebti, 2009)…”
Section: Ramanujan-fourier Transformmentioning
confidence: 99%
“…The shape of the received signal reflected by all particles met by the transmitted beam is: [3], [5], [8].…”
Section: Estimation Theorymentioning
confidence: 99%